Effect of Administration of Neuromuscular Blocking Agents in Children With Severe Traumatic Brain Injury on Acute Complication Rates and Outcomes: A Secondary Analysis From a Randomized, Controlled Trial of Therapeutic Hypothermia. Issue 4 (May 2015) - Chin, Katherine H.; Bell, Michael J.; Wisniewski, Stephen R.; Balasubramani, Goundappa K.; Kochanek, Patrick M.; Beers, Sue R.; Brown, S. Danielle; Adelson, P. David
Abstract : Objective: To evaluate the association between neuromuscular blocking agents and outcome, intracranial pressure, and medical complications in children with severe traumatic brain injury. Design: A secondary analysis of a randomized, controlled trial of therapeutic hypothermia. Setting: Seventeen hospitals in the United States, Australia, and New Zealand. Patients: Children (< 18 yr) with severe traumatic brain injury. Interventions: None for this secondary analysis. Measurements and Main Results: Children received neuromuscular blocking agent on the majority of days of the study (69.6%), and the modified Pediatric Intensity Level of Therapy scores (modified by removing neuromuscular blocking agent administration from the score) were increased on days when neuromuscular blocking agents were used (9.67 ± 0.21 vs 5.48 ± 0.26; p < 0.001). Children were stratified into groups based on exposure to neuromuscular blocking agents (group 1 received neuromuscular blocking agents each study day; group 2 did not). Group 1 had increased number of daily intracranial pressure readings more than 20 mm Hg (4.4 ± 1.1 vs 2.4 ± 0.5; p = 0.015) and longer ICU and hospital length of stay ( p = 0.003 and 0.07, respectively, Kaplan-Meier). The Glasgow Outcome Score-Extended for Pediatrics at hospital discharge and 3, 6, and 12 months after traumatic brain injury and medical complications observed during the acute hospitalization were similar between groups. Conclusions: Administration of neuromuscular blocking agents was ubiquitous and daily administration of neuromuscular blocking agents was associated with intracranial hypertension but not outcomes—likely indicating that increased injury severity prompted their use. Despite this, neuromuscular blocking agent use was not associated with complications. A different study design—perhaps using randomization or methodologies—of a larger cohort will be required to determine if neuromuscular blocking agent use is helpful after severe traumatic brain injury in children.